2021
DOI: 10.15252/embj.2020106061
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine‐synthesizing macrophages in subcutaneous fat are regulated by β 2 ‐adrenergic signaling

Abstract: Non-neuronal cholinergic signaling, mediated by acetylcholine, plays important roles in physiological processes including inflammation and immunity. Our group first discovered evidence of non-neuronal cholinergic circuitry in adipose tissue, whereby immune cells secrete acetylcholine to activate beige adipocytes during adaptive thermogenesis. Here, we reveal that macrophages are the cellular protagonists responsible for secreting acetylcholine to regulate thermogenic activation in subcutaneous fat, and we term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 54 publications
2
37
0
Order By: Relevance
“…Besides sympathetic innervation or denervation, the local noradrenergic tone within thermogenic adipose tissues has been proposed to be mediated by adipose resident immune cells, such as subpopulations of ATM synthesizing or degrading catecholamine ( 17 , 19 ). Intriguingly, recent studies also identified cholinergic adipose macrophages (ChAMs) that secrete acetylcholine to selectively activate beige fat thermogenesis under cold exposure ( 15 ). Hence, the regulation and function of thermogenic fat need to be understood considering its heterogeneity and complexity stemming from the tissue microenvironment as a bona fide platform for developing thermogenic fat-targeting therapeutic interventions.…”
Section: A Distinct Role Of Thermogenic Fat In Energy Homeostasismentioning
confidence: 99%
See 3 more Smart Citations
“…Besides sympathetic innervation or denervation, the local noradrenergic tone within thermogenic adipose tissues has been proposed to be mediated by adipose resident immune cells, such as subpopulations of ATM synthesizing or degrading catecholamine ( 17 , 19 ). Intriguingly, recent studies also identified cholinergic adipose macrophages (ChAMs) that secrete acetylcholine to selectively activate beige fat thermogenesis under cold exposure ( 15 ). Hence, the regulation and function of thermogenic fat need to be understood considering its heterogeneity and complexity stemming from the tissue microenvironment as a bona fide platform for developing thermogenic fat-targeting therapeutic interventions.…”
Section: A Distinct Role Of Thermogenic Fat In Energy Homeostasismentioning
confidence: 99%
“…Jun et al. recently identified ChAMs responsible for acetylcholine secretion and adaptive thermogenesis in subcutaneous WAT where parasympathetic innervation is absent ( 15 , 92 , 93 ). Using ChAT reporter mice to monitor functional ChAT-expressing cells in vivo , acetylcholine-producing cell populations were defined as CD45 + hematopoietic immune cells, not neurons, and they were composed mainly of B cells, T cells and macrophages ( 92 ).…”
Section: The Adipose Macrophages Central To Adaptive Thermoregulationmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, a study pointed out CX3CR1 + SAMs as a potential source of IL-27, which has been shown to contribute to thermogenesis and energy expenditure ( 75 ). Besides, a novel study proposed a subpopulation termed cholinergic adipose macrophages (ChAMs) to secrete acetylcholine and regulate thermogenic activation of beige fat ( 41 ), adding another layer of complexity to the global contribution of macrophages to sympathetic activation. The sufficiency of M2 macrophages in promoting browning independently of sympathetic neuron involvement was described in a Fasn -/- mouse model ( 76 ).…”
Section: Understanding the Roles Of Immune Cells In Thermogenic Adipo...mentioning
confidence: 99%